Stresle başaçıkma tarzlarının üniversite öğrencilerinde olumsuz otomatik düşünceler, transaksiyonel analiz ego durumları ve bazı değişkenler açısından incelenmesi - Akbağ, Müge (My University, 2000)
The main purpose of this research is to examine the relationship between coping styles and negative automatic thoughts and ego states of university students. Some other independent variables such as sex, grade level, income level, education levels of mother and father, perceived parental attitude were also examined in terms of their relations to coping styles, negative automatic thoughts and ego states. Survey method was used in this research. The sample of the research was consisted of 1382 students from the first and last grades of different faculties of Marmara University. Four instruments were used to collect data. These are: (1) Personal Information Form, developed by researcher, (2) Coping Style Scale, derived from the Ways of Coping Inventory of Folkman and Lazarus by Şahin and Durak (1995), (3) Automatic Thoughts Scale, adapted by Aydın and Aydın (1990) and, Şahin and Şahin (1992), (4) Ego State Scale, developed by Arı (1989). Pearson Product Moments Correlation Coefficient, Independent Sample of t Test, F Test (One Way ANOVA) are the statistical techniques used in the research according to the type of the variables and the purpose of the research. Scheffe and Tukey-Kramer Tests were also used after F Test, when significant differences were found. Significance level was accepted as 0.05. Some major findings of the research are: There is a significant relationship between coping styles of students and negative automatic thoughts. It is understood that the level of negative automatic thoughts was negatively correlated with coping styles of self-confident style, optimistic style and seeking of social support but was positively correlated with helpless style and submissive style. There is a significant relationship between negative automatic thought levels and ego states of students. This result indicates that the level of negative automatic thoughts was positively correlated with Critical Parent and Adapted Child ego state scores but was negatively correlated with Nurturing Parent, Adult and Free Child ego state scores. The Ego State Scale was administered to the students and the egograms were derived for each student and then the students were also classified according to the highest scores of the egogram. Based on this classification, negative automatic thought levels of students were compared with their ego states. The comparison between these variables showed that the students who were in Adapted Child ego state had the highest scores from negative automatic thoughts and the students who were in Adult ego state had also the lowest scores from negative automatic thoughts. The relationship between ego states and coping styles were also examined. It was found that self-confident style, optimistic style which are problem-oriented and effective in coping with problems, and seeking of social support were negatively correlated with Critical Parent and Adapted Child ego state scores but were positively correlated with Nurturing Parent, Adult and Free Child ego state scores. Helpless style and submissive style which are emotion-oriented and ineffective in coping with problems, were positively correlated with Adapted Child, Critical Parent ego state scores but were negatively correlated with Nurturing Parent, Adult and Free Child ego state scores. The students were classified according to their highest scores obtained from the egogram. Based on this classification, coping styles of students were compared with their ego states. The results indicates that the students who were in Adult ego state had the highest scores from the self-confident style. On the other hand, the students who were in Adapted Child ego state had the lowest scores from self-confident style. The students who were in Adult ego state had the highest scores from optimistic style were followed by the students who were in Nurturing Parent ego state. The students who were in Critical Parent ego state had the lowest scores from optimistic style were followed by the students who were in Adapted Child ego state. Helpless and submissive styles were mostly preferred by students in Adapted Child ego state and were least preferred by students in Adult ego state to cope with the psychological stress. The students who were in Free Child ego state had the highest scores from seeking of social support were followed by the students in Nurturing Parent ego state. The students who were in Critical Parent ego state had the lowest scores from seeking of social support were followed by the students in Adapted Child ego state. Briefly, the findings of correlative and comparative statistical analysis to examine the relationship between ego states and negative automatic thoughts and coping styles were found to be consistent. In this research it was also examined that if negative automatic thoughts, ego states and coping styles were differentiated according to sex, grade level, income level, education levels of mother and father and perceived parental attitude. The results showed that although negative automatic thought levels were not affected by sex, it was affected by grade level, income level, education levels of mother and father and perceived parental attitude. The same independent variables mentioned above were examined with ego state scores. A statistically significant difference was found only on Adult ego state scores in favour of male students. Another significant difference was found on Adapted Child ego state scores according to the grade levels in favour of 1st grade level. Some differences were also found on Adapted Child, Adult, Free Child ego state scores according to income level. Education levels of mothers and fathers were two other independent variables to be examined. The findings showed that some differences were found on Free Child and Adapted Child ego state scores according to mothers' education level. On the other hand, the only difference was found on Free Child ego state scores according to the education level of fathers. Five ego state scores examined in this research were also found to be affected by perceived parental attitudes. Another research question was to examine the differences between coping styles and other independent variables such as sex, grade level, income level, education levels of mother and father, perceived parental attitude. Optimistic style, helpless style and seeking of social support were affected by sex. While optimistic style was mostly preferred by male students, helpless style and seeking of social support were mostly preferred by female ones. Grade level had not an effective role on coping styles. Self-confident, helpless, submissive styles and seeking of social support scores showed differences according to income level. Self-confident, helpless, submissive styles and seeking of social support scores were found to be differentiated according to the education level of mothers, on the other hand only self-confident and submissive styles scores showed differences according to the education level of fathers. Perceived parental attitudes were to be found as an effective variable on coping styles. All these findings were discussed in the light of the current literature.
Keywords: Heyecanlar ve duygular; Psikoloji; Stres (Psikoloji)